Rethinking English language testing in the post-Covid era: Integrating online testing in EFL classes - SAIHI, Hanane (Social Sciences Journal, 2023)
The global pandemic impacts the learning process as well as its assessment, for it altered the traditional classroom portrait from face to face to the virtual classroom. This new premise pushed the teachers to rethink how to evaluate their students by keeping their lives safe. In this paper, we sought to uncover the teachers’ attitudes toward the online assessment of their students at Biskra University. To achieve this objective, we administered an online mixed questionnaire. The responses showed that the teachers have a positive view towards the use of online assessment if they can overcome obstacles which are mainly related to the lack of knowledge and experience in using IT among both teachers and their students. Moreover, they spotted the light on the problem of internet connection for test-takers living in remote locations. Yet, the respondents who have a negative view justified that online assessment affects the selection of test item type, and this will negatively affect the test validity. The research findings did confirm that there are controversial views among Biskra University teachers towards the adoption of online assessment in the post-pandemic era. This recommends rethinking the position of online assessment and its effectiveness after Covid-19.